A New Digital Solution Helps Automatic Voice Recognition - ABOULKHIR, M; BOUREKKADI, S; KHOULJI, S; SLIMANI, K; L. KERKEB, M (International Journal of Engineering and Technology, 2018)
This scientific work concerning an examination on automatic speech recognition (ASR) frameworks connected with the home automation and to express the importance of this academic work, an itemized investigation of the engineering of speech recognition frameworks was completed. Our goal in Information Systems Engineering Research Group ofAbdelmalekEssaadi University is to choose a speech recognition programming that must work in remote speech conditions and in a rowdy area.The proposed framework is using atoolbox called Kaldi, which must correspond as aclient created by an advanced programming language, with any home automation framework.Â